The rare Fuegian fox (Lycalopex culpaeus) from the Tierra del Fuego Archipelago: history of discovery, geographic distribution, and socio-ecological aspects - Fabian M. Jaksic; Carlos Zurita; Cristóbal Briceño; Jaime E. Jiménez (Revista Chilena de Historia Natural, 2024)
Abstract Background The Fuegian fox (Lycalopex culpaeus) is a rare inhabitant of the Tierra del Fuego Archipelago on account of: (a) It is the southernmost Canid in the world. (b) It is the second largest, heaviest, and tallest native Canid in South America. (c) It is currently scarce in northern Tierra del Fuego. (d) It may have been tamed by the Selk’nam natives. Methods and results Based on chronicles and scientific reports we document the timeline since discovery of the distinctive and island-confined Fuegian fox. We pay attention to its patchwork distribution within the Fuegian archipelago, with populations spread on the large Tierra del Fuego Island (Fuegia) and on two smaller ones, Hoste and Gable. This fox seems to have disappeared recently from the latter and historic records from Navarino Island are dubious. We provide new distributional records and unpublished photographs. Among the socio-ecological aspects studied, we highlight the relationships of this fox with two local indigenous people: The Yahgan and the Selk´nam. Discussion The introduction of sheep Ovis aries in 1885 and the ensuing persecution of its putative predators apparently caused the fox decline from the northern half of Fuegia. The introduction of the continental Chilla fox Lycalopex griseus in 1951 further impacted the Fuegian fox, apparently by competition for food but perhaps also by diseases. It is currently concentrated in the southern half of Tierra del Fuego Island. The possibility that the Selk’nam introduced this fox from the mainland and that they tamed it, is also discussed.